2021
DOI: 10.1111/jfb.14965
|View full text |Cite
|
Sign up to set email alerts
|

Association of predation risk with a heterospecific vocalization by an anabantoid fish

Abstract: Honey gouramis (Trichogaster chuna) received chemical alarm cues derived from conspecific epidermal tissue and, simultaneously, the vocalization produced by a heterospecific gourami species, the sparkling pygmy gourami (Trichopsis pumila). Control trials paired water with the vocalization. In trials that received alarm cues, honey gouramis significantly increased activity relative to control trials that received water, suggesting an attempt to flee and search for refuge. When the recording of the vocalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
(39 reference statements)
2
4
0
Order By: Relevance
“…Zebrafish conditioned with alarm cues and a three-note auditory stimulus responded with antipredator behaviour when re-exposed to either the same three-note stimulus, or two of the three notes, relative to a playback stimulus containing only one of the three notes. These data corroborate earlier studies that demonstrated that fishes can associate risk with auditory stimuli (Wisenden et al, 2008;Seigel et al, 2021Seigel et al, , 2022. Response intensity of learned responses were of lower intensity than behavioral responses during conditioning trials, manifest only as a significant change in vertical distribu- tion but not change in activity or shelter use.…”
Section: Discussionsupporting
confidence: 90%
“…Zebrafish conditioned with alarm cues and a three-note auditory stimulus responded with antipredator behaviour when re-exposed to either the same three-note stimulus, or two of the three notes, relative to a playback stimulus containing only one of the three notes. These data corroborate earlier studies that demonstrated that fishes can associate risk with auditory stimuli (Wisenden et al, 2008;Seigel et al, 2021Seigel et al, , 2022. Response intensity of learned responses were of lower intensity than behavioral responses during conditioning trials, manifest only as a significant change in vertical distribu- tion but not change in activity or shelter use.…”
Section: Discussionsupporting
confidence: 90%
“…Besides increased cohesion, polarization and velocity, freezing is another strategy often adopted by prey, to avoid a predator. A variety of fish species, including zebrafish, are known to exhibit freezing behaviour in presence of a predator (Seigel et al 2022, Kimbell and Morell 2015; Kalueff et al 2013; Malavasi et al 2013; Brown and Magnavacca 2003, Brown and Dreier 2002). Further, freezing has been shown to increase proportionally with increase in dosage of alarm substance, i.e, predator cue (Speedie and Gerlai 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been demonstrated that some fish can associate risk with auditory stimuli when a novel auditory stimulus is paired with chemical alarm cues released from damaged epidermis (e.g., Johnson et al, 2023;Seigel et al, 2021Seigel et al, , 2022Wisenden et al, 2008). Fathead minnows Pimephales promelas and glowlight tetras Hemigrammus erythrozonus learn to associate risk with a tone when the tone and conspecific alarm cues from damaged skin of conspecifics are presented simultaneously (Wisenden et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish (minnow family) also associate risk with a tone and respond specifically to the frequency of the training tone and do not respond to tones of different frequencies (Seigel et al, 2021). Honey gouramis Trichogaster chuna (an anabantoid) can be trained to associate risk of predation with the call of a heterospecific anabantoid, the sparkling gourami Trichopsis pumila (Seigel et al, 2022), suggesting a plausible path for the evolution of an auditory alarm signal (Wisenden, 2014b). Seigel et al (2022) did not record auditory responses of test subjects because honey gouramis are not known to produce sounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation